Characterization of Non-hormone Expressing Endocrine Cells in Fetal and Infant Human Pancreas - Moin, Abu Saleh Md; Montemurro, Chiara; Zeng, Kylie; Cory, Megan; Nguyen, Megan; Kulkarni, Shweta; Fritsch, Helga; Meier, Juris J.; Dhawan, Sangeeta; Rizza, Robert A.; Atkinson, Mark A.; Butler, Alexandra E. (Frontiers in Endocrinology, 2019)
Context: Previously, we identified chromograninA positive hormone-negative (CPHN) cells in high frequency in human fetal and neonatal pancreas, likely representing nascent endocrine precursor cells. Here, we characterize the putative endocrine fate and replicative status of these newly formed cells. Objective: To establish the replicative frequency and transcriptional identity of CPHN cells, extending our observation on CPHN cell frequency to a larger cohort of fetal and infant pancreas. Design, Setting, and Participants: 8 fetal, 19 infant autopsy pancreata were evaluated for CPHN cell frequency; 12 fetal, 24 infant/child pancreata were evaluated for CPHN replication and identity. Results: CPHN cell frequency decreased 84% (islets) and 42% (clusters) from fetal to infant life. CPHN cells rarely replicate, unlike the beta-cells at this stage. While the majority of CPHN cells express (in overall compartments of pancreas) the pan-endocrine transcription factor NKX2.2 and beta-cell specific NKX6.1 in comparable frequency in fetal and infant/child cases (81.9±6.3 vs 82.8±3.8% NKX6.1+-CPHN cells of total CPHN cells, fetal vs infant/child, p=0.9; 88.0±4.7 vs 82.1±5.3% NKX2.2+-CPHN cells of total CPHN cells, fetal vs infant/child, p=0.4), the frequency of clustered CPHN cells expressing NKX6.1 or NKX2.2 is lower in infant/child vs fetal cases (1.2±0.3 vs 16.7±4.7 clustered NKX6.1+-CPHN cells/mm2, infant/child vs fetal, p<0.01; 2.7±1.0 vs 16.0±4.0 clustered NKX2.2+-CPHN cells/mm2, infant/child vs fetal, p< 0.01). Conclusions: The frequency of CPHN cells declines steeply from fetal to infant life, presumably as they differentiate to hormone-expressing cells. CPHN cells likely represent a non-replicative pool of endocrine precursor cells, largely fated to become beta-cells.